Randomized experimental study of two novel techniques for transanal repair of dehiscent low rectal anastomosis - Kalvach, J; Ryska, O; Martinek, J; Hucl, T; Pazin, J; Hadac, J; Foltan, O; Kristianova, H; Ptacnik, J; Juhasova, J; Ryska, M; Juhas, S (Surgical endoscopy, 2022)
BACKGROUND: Anastomotic leak after low anterior rectal resection is a dreadful complication. Early diagnosis, prompt management of sepsis followed by closure of anastomotic defect may increase chances of anastomotic salvage. In this randomized experimental study, we evaluated two different methods of trans-anal anastomotic repair. METHODS: A model of anastomotic leak was created in 42 male pigs. Laparoscopic low anterior resection was performed with anastomosis created using a circular stapler with half of the staples removed. Two days later, animals were randomized into a TAMIS (trans-anal minimally invasive surgery) repair, endoscopic suture (ENDO) or control group with no treatment (CONTROL). Signs of intraabdominal infection (IAI), macroscopic anastomotic healing and burst tests were evaluated to assess closure quality after animals were sacrificed on the ninth postoperative day. RESULTS: Closure was technically feasible in all 28 animals. Two animals had to be euthanized due to progressive sepsis at four and five days after endoscopic closure. Healed anastomosis with no visible defect was observed in 10/14 and 11/14 animals in TAMIS and ENDO groups, respectively, versus 2/14 in CONTROL (p < 0.05). Overall IAI rate was significantly lower in TAMIS (4/14; p = 0.006) and ENDO (5/14; p = 0.018) compared to CONTROL (12/14). Burst tests confirmed sealed closure in healed anastomosis with a median failure pressure of 190 (110-300) mmHg in TAMIS and 200 (100-300) mmHg in ENDO group (p = 0.644). CONCLUSION: In this randomized experimental study, we found that both evaluated techniques are effective in early repair of dehiscent colorectal anastomosis with a high healing rate.
Keywords: Anastomosis; netěsnost anastomózy; anastomóza chirurgická; Humans; Sepsis; Female; Anastomosis, Surgical; Rectum; sepse; lidé; zvířata; nádory rekta; Swine; ženské pohlaví; Rectal Neoplasms; Male; New techniques; Anastomotic Leak; Dehiscence; Animals; rektum; mužské pohlaví; Closure; prasata